2021
DOI: 10.3390/biom11050765
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential (TRP) Channels in Haematological Malignancies: An Update

Abstract: Transient receptor potential (TRP) channels are improving their importance in different cancers, becoming suitable as promising candidates for precision medicine. Their important contribution in calcium trafficking inside and outside cells is coming to light from many papers published so far. Encouraging results on the correlation between TRP and overall survival (OS) and progression-free survival (PFS) in cancer patients are available, and there are as many promising data from in vitro studies. For what conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Few data are present about the involvement of TRP channels in hematological malignancies. The expression of several members of the TRP family in different lymphoid and myeloid leukemia has been demonstrated 5,6 . In fact, it has been shown that TRPV5 and 6‐induced [Ca 2+ ] i stimulates cell cycle arrest in myeloid leukemia cell lines 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few data are present about the involvement of TRP channels in hematological malignancies. The expression of several members of the TRP family in different lymphoid and myeloid leukemia has been demonstrated 5,6 . In fact, it has been shown that TRPV5 and 6‐induced [Ca 2+ ] i stimulates cell cycle arrest in myeloid leukemia cell lines 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of several members of the TRP family in different lymphoid and myeloid leukemia has been demonstrated. 5 , 6 In fact, it has been shown that TRPV5 and 6‐induced [Ca 2+ ] i stimulates cell cycle arrest in myeloid leukemia cell lines. 7 The inhibition of TRPM7 reduces cell proliferation and promotes erythroid differentiation in K562 CML cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the primary physiological roles of TRP channels are perception of various sensations ranging from pain, pressure, temperature, taste and vision. However, evidence accumulates that TRP channels also regulate proliferation, differentiation, invasion, metastasis, autophagy and apoptosis of malignant cells (80,81,(166)(167)(168)(169)(170). TRP channels have been shown to contribute crucial oncogenic functions in a number of hematologic malignancies (166,167).…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 99%
“…However, evidence accumulates that TRP channels also regulate proliferation, differentiation, invasion, metastasis, autophagy and apoptosis of malignant cells (80,81,(166)(167)(168)(169)(170). TRP channels have been shown to contribute crucial oncogenic functions in a number of hematologic malignancies (166,167). Leukemia, lymphoma, myeloma and Waldenström macroglobulinaemia patient cells and cell lines have altered expression of TRP channels that has been linked with changes in cell proliferation, cell death and cell migration (165-167) (Table 1).…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 99%
“…Breast cancer progression is reported to be supported by TRPV6 and more so by the gain-of-function R532Q mutant of TRPV6 ( 2 ). TRP channel overexpression has also been implicated in hematopoietic malignancies such as leukemia and lymphoma ( 3, 4 ). In colorectal cancers, TRP channels are reported to be overexpressed and responsible for facilitating metastasis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%